Penanganan Pekerja Migran Indonesia Non-Prosedural dalam Perspektif Hukum Keimigrasian - Apri Tri Longgarini; Aulia Nurul Shaafiyah; Bella Mega Rahmaningtias (Universitas Batanghari Jambi, 2023)
Indonesia is one of the largest migrant workers producers in ASEAN. The large numbers of Indonesian people who are involved become Indonesian Migrant Workers or IMWs start to get fretful, because non-procedural IMWs operate without valid or incomplete documents. The appearance of non-procedural IMWs presents a greater risk of crime that may occur to migrant workers, considering they are non-procedural IMWs who are not bound or protected by the law regulates Indonesian overseas workers, such as Law no. 18 of 2017. Insufficient coverage of the legal basis, as well as a lack of general knowledge about the law and the consequences of its violations, and as well as weak law enforcement are the main reasons for the circulation of non-procedural IMWs who become possible crimes victims such as exploitation, harassment, discrimination, smuggling and human trafficking to become homicide victims eventually. The Immigration Department is one of the government agencies related to IMWs, carries out its duties as part of public service providers and law enforcement. Law enforcement carried out by immigration authorities in the form of enforcing threats through criminal proceedings is a form of law enforcement carried out by immigration to protect IMWs and prevent the release of non-procedural PMI information. This research was motivated by the author's concern about IMWs problems consider the immigration sector is one of the most important aspects in the development of the country in accordance with the immigration function. This research used a normative legal method based on a literature review and a policies comparison with qualitative data. The policy, political and technical innovations are expected to contribute to the existence of non-procedural migrant workers both legally and socially.